2019
DOI: 10.1002/rrq.257
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Awareness of Cross‐Language Suffix Correspondences in Second‐Language Reading Comprehension

Abstract: A B S T R A C TUnderstanding text in a second language can be particularly challenging. The authors explored the contribution of morphological awareness in children's first and second languages to development in second-language reading comprehension. Critically, the authors examined the role of a skill that might be at the heart of these cross-linguistic connections: awareness of crosslanguage suffix correspondences. This is the awareness, for instance, that the French suffix -eux and the English suffix -ous h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 67 publications
(95 reference statements)
0
11
0
Order By: Relevance
“…These studies indicate differences depending on whether one assesses morphological awareness, morphological decoding or morphological analysis. Lam, Chen, and Deacon (2020) further support this, with suffix awareness contributing uniquely to L2 reading comprehension. Clearly, an assessment of morphological knowledge must assess various morphological skills.…”
Section: Why Morphological Knowledge? Connections To Researchmentioning
confidence: 83%
“…These studies indicate differences depending on whether one assesses morphological awareness, morphological decoding or morphological analysis. Lam, Chen, and Deacon (2020) further support this, with suffix awareness contributing uniquely to L2 reading comprehension. Clearly, an assessment of morphological knowledge must assess various morphological skills.…”
Section: Why Morphological Knowledge? Connections To Researchmentioning
confidence: 83%
“…In particular, little research on the SVR has focused on morphological process of fluent decoding discussed earlier in this article in light of L1 versus L2 readers’ differential experience in the target language, not to mention how variation may exist between L2 readers from different L1 backgrounds, for whom the influence from prior language and literacy processing experience is naturally expected (Koda, ). Such an influence or cross‐linguistic transfer effect, in addition to being supported by interlingual correlations between L1 and L2 in diverse groups of L2 or bilingual readers (e.g., Lam, Chen, & Deacon, ), has been well documented in Koda and colleagues’ studies that compared written word recognition or lexical processing in adult learners of English as a second language (ESL) with disparate L1 backgrounds (e.g., Hamada & Koda, ; Muljani, Koda, & Moates, ; Wang & Koda, ). Those studies overall found that as compared with ESL readers whose L1 was Chinese, which uses a morphosyllabic writing system, those readers whose L1 was alphabetic (e.g., Indonesian) consistently showed a processing advantage, in terms of faster responses, in lexical decision tasks that tapped sensitivity to English letter–phoneme mapping patterns.…”
Section: Morphology Lexical Quality and L2/bilingual Readersmentioning
confidence: 97%
“…Researchers (Kuo & Anderson, 2006;Jeon, 2011;Wade-Woolley & Geva, 1999;Carlisle, 2000;Haomin & Koda, 2018; argued that recognizing morphological structure in words can be helpful to the reader in understanding the functions of unfamiliar words in reading comprehension across languages as well as within languages, and they proposed the aspect of morphological awareness transfer to be considered in studies of language learning and teaching. In reading literature, it has been suggested that morphological awareness is cross-linguistically related to reading comprehension in different languages (L1 and L2) which have similar morphological structures and noticeably different morphological structures (Ramírez, Chen, & Pasquarella, 2013;Lam, Chen, & Deacon, 2020;Vaknin-Nusbaum, & Saiegh-Haddad, 2020;Wang et al, 2006;Wang et al, 2009;Schiff & Calif, 2007). However, only a few pairs of languages have been studied so far: English and Arabic (Saiegh-Haddad & Geva, 2008), English and Korean (Wang et al, 2009), Spanish and English (Ramrez et al, 2013), and Chinese and English (Jie et al, 2010;Wang et al, 2006. For instance, among Korean students speaking English as a second language, Wang et al, (2009) investigated the cross-linguistic morphological associations with word reading and reading comprehension.…”
Section: Literature Reviewmentioning
confidence: 99%